The Evolution of Cyber Law: Protecting Privacy and Data in the Digital Age - Dzakiyyatul Alifah (ASIAN PUBLISHER, 2024)
In the digital era, the rapid advancement of technology has brought both unprecedented convenience and significant legal challenges. As personal data becomes increasingly vulnerable to breaches, misuse, and surveillance, the field of cyber law has emerged as a critical framework to safeguard digital privacy and security. This article explores the historical development and current state of cyber law, focusing on how legal systems across the globe are adapting to address cybercrimes, data protection, and user privacy. It also examines landmark legislations, such as the General Data Protection Regulation (GDPR) and other national-level statutes, while highlighting the ongoing need for international cooperation and dynamic legal reforms. The study emphasizes the importance of educating users and policymakers on digital rights, and it underscores the role of law in fostering a secure digital environment in an increasingly interconnected world.